Spatio-temporal variation and conservation priorities of wilderness in Lhasa River Basin, Tibetan Plateau - Wang, Li; Fu, Jia; Ji, Xiaopan; Tan, Ping; Li, Yike (Frontiers in Ecology and Evolution, 2023)
Wilderness plays a crucial role in biodiversity conservation, and its preservation represents a pivotal objective emphasized in the Post-2020 Global Biodiversity Framework (GBF). Nonetheless, wilderness frequently faces threats from the escalating impact of human activities, leading to significant repercussions on diverse ecological processes. Despite the abundance of previous studies on wilderness, there has been a limited focus on the temporal dynamics at the local scale, as well as on identifying the conservation priorities in terms of their ecosystem services. In this study, taking the Lhasa River Basin in the Qinghai-Tibet Plateau of China as an example, the spatio-temporal variations of wilderness were analyzed, and conservation priorities of them were further identified based on ecosystem services. The results revealed a persistent decline in the wilderness from 1990 to 2020, particularly in terms of bare land and grassland. Furthermore, we identified that 33.56% of the remaining wilderness necessitated special attention. These findings offer valuable insights into potential future threats to wilderness and hold critical importance for formulating regional conservation strategies at the local scale.